Membangun Rasa Percaya Diri Anak-Anak Panti Melalui Pembelajaran Matematika - Yulia Ramadani; Hairani Siregar (Yayasan Literasi Sains Indonesia, 2022)
Self-confidence is one of the most important aspects of a person's personality. Self-confidence is a very valuable attribute in a person in social life, without self-confidence it will cause many problems in a person. Confidence is something that is important for every individual to have. Confidence is needed by both a child and a parent, individually or in a group. Confidence does not just appear in a person, but there is a certain process in the person so that the formation of self-confidence occurs, which is not an instant process but through a long process that took place from an early age. Without realizing it, a lack of self-confidence in someone can be detrimental to himself. As experienced by one of the children at the Pintu Harapan Orphanage who lacked confidence in school, making the child less understanding of mathematics. And really needs help to increase his confidence in himself. The process of providing assistance is carried out in the PKL 1 mini project activity, namely by using the casework method as a social work technique approach aimed at helping individuals who have problems with face-to-face services. Several stages consist of Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and the last stage is Termination. The focus of solving the client's problem is to convince the client to be confident so that he is more daring to ask the teacher and his classmates about lessons that are difficult to understand. The purpose of this strategy was declared successful with significant changes in the client, including in the learning process that increased confidence in him.